Presumed unconstrained dispersal of Aedes aegypti in the city of Rio de Janeiro, Brazil - Maciel-de-Freitas, Rafael (2009)
OBJECTIVE: To evaluate dispersal of Aedes aegypti females in an area with no container manipulation and no geographic barriers to constrain mosquito flight. METHODS: A mark-release-recapture experiment was conducted in December 2006, in the dengue endemic urban district of Olaria in Rio de Janeiro, Southeastern Brazil, where there is no evident obstacle to the dispersal of Ae. aegypti females. Mosquito traps were installed in 192 houses (96 Adultraps and 96 MosquiTRAPs). RESULTS: A total of 725 dust-marked gravid females were released and recapture rate was 6.3%. Ae. aegypti females traveled a mean distance of 288.12 m and their maximum displacement was 690 m; 50% and 90% of females flew up to 350 m and 500.2 m, respectively. CONCLUSIONS: Dispersal of Ae. aegypti females in Olaria was higher than in areas with physical and geographical barriers. There was no evidence of a preferred direction during mosquito flight, which was considered random or uniform from the release point.